The Effect of Education Game as a Learning Media for Students Achievement in the Covid 19 Pandemic Era - Ikhwatul Hasan; Rizal Amri; Dimas Pratama (Pancaran Pendidikan, 2020)
In this globalization era learning systems or learning media must be adapted to the times, therefore teachers or educators are required to be able to make a technological innovation in teaching and learning activities, it aims to make the material and learning well delivered to students. Seeing the current conditions many students are shackled by the sophistication of the virtual world that can be seen from the active students on social media, as well as playing games. So that not a few of those who forget the obligation to learn and become a serious problem for the world of education in the future.This research is expected to make students interested in learning by using game media, because they look at the development and progress of the era in the current era, many students who take advantage of their time or use their free time to play games via Android or computer. Therefore, with this educational game students can play while learning, which of course contains material that is in accordance with KI KD in the curriculum and as a parameter for students to understand the material being taught.